(untitled) (Research, Society and Development, 2022)
The Corona Virus Disease 2019 (COVID-19) pandemic has caused moments of uncertainty, neutralized economic activities, and adapted routine practices. However, some business segments are not prepared to respond quickly to eventualities, especially Micro and Small Enterprises (MSE’s). This article’s central element was to identify the types of behavior of entrepreneurs and consumers of micro and small gyms in adapting physical activity practices in times of a pandemic. We choose the fitness context because it is one of the sectors of the economy that was the most financially impacted due to social isolation, prohibition of agglomeration of people, and dependence on physical space to carry out activities. Through a methodology based on netnography, during the winter of 2020, data from the profiles of the Instagram social network of 42 gyms, 7 personal trainers, and 28 consumers were collected and analyzed, in addition to 13 hashtags. As a result, we found four types of behaviors of entrepreneurs and consumers: adaptor, resilient, quitter, and denier. We believe that this article will contribute to the understanding of MPE’s changes and adaptations in moments of uncertainty. From the perspective of fitness center entrepreneurs and their consumers, the findings from the survey highlight that the pandemic was a means for the sector to improve the way it offered the service through the addition of new habits and consumption needs that could point to new post-pandemic routines and trends.